Republic of Korea : Report on Observance of Standards and Codes; Data Module. (IMF Staff Country Reports; Country Report ;, 2010)
Korea's statistics are generally of a high quality, and reflect a significant improvement since the last Report on the Observance of Standards and Codes. Korea's adherence to internationally accepted statistical practices requires cross-cutting recommendations, and the development of a national publication dedicated to the dissemination of data and metadata for general government. For monetary statistics purposes, valuing all marketable financial instruments in the Bank of Korea (BOK) balance sheet and aligning the basis of recording of income transactions to that recommended by international standards is required.